Control rectifier for variable speed single phase DC motor - Mohd Helmi, Samta (2008)
An electric power can be converted from one form to another form by using power electronics devices. The function of power electronics circuits by using semiconductor devices as switch is modifying or controlling a voltage. The goal of power electronics circuits are to convert electrical energy from one form to another, from source to load with highest efficiency, high availability and high reliability with the lowest cost, smallest size and weight. The term rectification refers to the power circuit whose function is to alter the ac characteristic of the line electric power to produce a “rectified”ac power at the load side that contain the dc value. In this project task, the rectifier circuit should be possible to produce a variable average voltage by controlling the delay. The single phase 240 Vrms AC source is stepped down to 12 Vrms by using step-down power transformer. A versatile method of controlling the output of a full-wave rectifier is to substitute controlled switches such as SCRs for the diodes. The output is controlled by adjusting the delay angle of each SCR, resulting in an output voltage or output current which is variable over a limited range with programmed the microcontroller.